2000
DOI: 10.1063/1.126396
|View full text |Cite
|
Sign up to set email alerts
|

Porous silicon microcavities as optical chemical sensors

Abstract: The optical properties of porous silicon microcavities are strongly dependent on the environment. For highly luminescent samples, both the luminescence intensity and the peak position are affected by organic substances, giving the possibility to obtain dual-parameter optical sensors. While the peak position depends on the organic compound refractive index, luminescence intensity depends on its low-frequency dielectric constant. This allows the discrimination between different organic substances. This sensor is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
135
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(138 citation statements)
references
References 11 publications
2
135
0
1
Order By: Relevance
“…Label-free sensors are important, not only because they avoid expensive and laborious labeling steps, but also because the labels may affect the biochemical recognition. So far, various label-free (bio) chemical sensors have been demonstrated, capable of measuring the refractive index change of the environment with high resolution [1][2][3][4][5][6][7]. The most developed sensors are the Surface Plasmon Resonance [1] and Mach-Zehnder interferometer [2,3] based devices, that require a large sensing area (~mm 2 ) which is one of the main limitations for integrating these sensors in optical chips.…”
Section: Introductionmentioning
confidence: 99%
“…Label-free sensors are important, not only because they avoid expensive and laborious labeling steps, but also because the labels may affect the biochemical recognition. So far, various label-free (bio) chemical sensors have been demonstrated, capable of measuring the refractive index change of the environment with high resolution [1][2][3][4][5][6][7]. The most developed sensors are the Surface Plasmon Resonance [1] and Mach-Zehnder interferometer [2,3] based devices, that require a large sensing area (~mm 2 ) which is one of the main limitations for integrating these sensors in optical chips.…”
Section: Introductionmentioning
confidence: 99%
“…Highly doped (10 19 cm -3 ) p-or n-silicon anodized in aqueous HF solution usually forms mesopores with pore sizes from 20 nm to 50 nm (Figure 4 (a)). Several groups have demonstrated that complex optical devices can be designed with mesoporous silicon (Mulloni & Pavesi, 2000). In the case of lightly doped (below ~10 18 cm -3 ) p-type silicon, the porous size distribution is normally found in the range 1 -5 nm, in the lower limit for mesopores (Figure 4 (b)).…”
Section: Porous Silicon Morphologymentioning
confidence: 99%
“…Optical sensors based on porous mono/double layers, Bragg mirrors, luminescent and reflective microcavities (MCs) have been reported in literature. [16,[35][36][37][38][39][40] Also, it should be noted that TNT detection with the use of a PSi microcavity infiltrated with a fluorescent sensory polymer has previously been studied. [16] All the above features of PSi are critical for detection of trace levels of explosives, such as TNT and cyclotrimethylenetrinitramine (RDX), which exhibit very low pressures of saturated vapours (in the ppb to ppt range).…”
Section: Introductionmentioning
confidence: 99%